PENGARUH BIMBINGAN PRIBADI SOSIAL TERHADAP KEMAMPUAN PENYESUAIAN SOSIAL SISWA KELAS X DI SMAN 1 PRAYA TIMUR TAHUN PELAJARAN 2020/2021 - SAHMUN SAHMUN; MUJIBURRAHMAN MUJIBURRAHMAN; M. SAMSUL HADI (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2021)
The Influance of Social Personal Guidance on the Social Adjustment Ability in X The problem in this study is that there is poor social adjustment showing destructive attitudes, disturbing others, and excessive shame so that they do not want to hang out with other people. The formulation of the problem in this study is whether there is an Influance of Social Personal Guidance on the Social Adjustment Ability in X grade Students of SMAN 1 East Praya in the Academic Year 2020/2021. The purpose of this study was to determine Influance of Social Personal Guidance on the Social Adjustment Ability in X grade Students of SMAN 1 East Praya in the Academic Year 2020/2021. The sample used in this study were 18 people. The instrument used in collecting data is the questionnaire method as the main method, while the interview, observation and documentation methods are complementary methods. In this case the questionnaire was developed in terms of social adjustment. Data analysis using t-test. In accordance with the results of the analysis with a significant level of 5%, it turns out that the calculated "t" value is greater than the "t" table or (10.687>2.110). So, the null hypothesis (Ho) reads "There is Influance of Social Personal Guidance on the Social Adjustment Ability in X grade Students of SMAN 1 East Praya in the Academic Year 2020/2021." stated "rejected" while the alternative hypothesis (Ha) which reads "There is an Influance of Social Personal Guidance on the Social Adjustment Ability in X grade Students of SMAN 1 East Praya in the Academic Year 2020/2021." declared "accepted". So it can be concluded that this research is "significant".